Preparation method of high-entropy alloy catalyst for preparing glycollate through efficient selective electrooxidation of ethylene glycol
By using the high -entropy alloy catalyst PDPTBICUSN/C, the existing precious metal catalysts have low activity, high cost, and poor stability in the selective electrical oxidation of ethan glycol, and achieve efficient, selective and stable ethanol preparation. With potential commercialization prospects.
Patent Information
- Application Number
- CN202411784886.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-21
AI Technical Summary
The existing precious metal catalysts have problems of low activity, high cost and poor stability in selective electrooxidation of ethylene glycol, which limits their promotion in practical applications.
The high-entropy alloy catalyst PdPtBiCuSn/C is used to combine palladium, platinum, copper, bismuth, tin and other elements with activated carbon to form a high-entropy alloy nanoparticle catalyst loaded on activated carbon balls.
The selection of ethylene glycol selected electrochemicals into ethanol acid salts was achieved by efficient, selectivity and stability. The electrochemical quality activity was significantly improved, the selectivity reached 98.69%, and the precious metal dosage was reduced.
Smart Images

Figure CN119332282A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing a high entropy alloy catalyst for preparing glycolate by selective electrooxidation of ethylene glycol, belonging to the technical field of electrocatalytic materials. Background Art
[0002] Ethylene glycol is not only a biomass platform molecule, but also a hydrolysis derivative of waste polyethylene terephthalate (PET) plastic. The green, sustainable and high-value conversion of ethylene glycol has significant economic benefits and environmental value. Ethylene glycol electrooxidation reaction (EGOR) is a complex multi-step proton-coupled electron transfer process that follows a dual-path reaction pathway. In this process, the C2 pathway (i.e., selective electrooxidation of ethylene glycol to glycolate, glyoxylate, etc.) is a key reaction pathway. Through the C2 pathway, ethylene glycol can be efficiently converted to obtain high-value-added chemicals, realizing the effective utilization of carbon cycle and promoting the development of green chemical industry. At present, noble metals (Pd, Pt, Au, etc.) and their oxides show excellent C2 pathway selectivity in EGOR. However, traditional noble metal catalysts usually have problems such as low activity, high catalyst cost and poor stability, which seriously restricts their promotion in practical applications. Therefore, the study of efficient, stable and inexpensive catalysts is of great significance to promote the development of selective electrooxidation of ethylene glycol to prepare high-value-added chemicals.
[0003] In recent years, high entropy alloys (HEAs), as a new type of multi-component material, have shown great potential in the field of electrocatalysis. HEAs are solid solutions composed of five or more main elements with similar atomic ratios. In order to expand the design range of alloys, the atomic ratio of each main element contained in HEAs can be in the range of 35% to 5%. High entropy alloys, with their complex crystal structure and rich surface chemical activity, provide a new idea for improving catalytic efficiency and stability. In the electro-oxidation reaction of ethylene glycol, high entropy alloy catalysts can not only improve the reaction rate and efficiency, but also have good stability. The introduction of multiple elements has greatly broadened the composition space, and its surface electronic structure and geometric structure can be regulated by adjusting the constituent elements, thereby optimizing the catalytic performance. The "high entropy effect" of high entropy alloys makes the structural entropy of high entropy alloys close to the mixing enthalpy under high temperature conditions, prompting the multi-element to form a single-phase solid solution and improving the thermodynamic stability of the catalyst. And the "lattice distortion effect" causes a large number of surface defects and unsaturated coordination sites to form on the catalyst surface, thereby exposing more active centers and promoting the activation and transfer of active substances. These properties help to provide multiple active sites for complex electrocatalytic reactions, thereby improving catalytic activity and anti-poisoning performance, which makes high-entropy alloy materials a key area of current catalyst research and have potential practical application value in the selective electrooxidation of ethylene glycol. Therefore, the present invention discloses a preparation method and application of a high-entropy alloy catalyst for the efficient selective electrooxidation of ethylene glycol to prepare glycolate. The high-entropy alloy nanoparticle catalyst is loaded on an activated carbon sphere with a high specific surface area. The prepared catalyst electrode has excellent performance in the selective electrooxidation of ethylene glycol to prepare glycolate in an alkaline environment, achieving the improvement of electrocatalytic performance while reducing the amount of precious metals used, and has potential commercial prospects. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electro-oxidation of ethylene glycol.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention discloses a method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electrooxidation of ethylene glycol, comprising the following steps:
[0007] 1) Weigh a certain proportion of palladium source, platinum source, copper source, bismuth source and tin source and dissolve them in a strong acid aqueous solution.
[0008] 2) Add activated carbon powder to the mixed solution and mix it evenly by ultrasonication to obtain a black suspension.
[0009] 3) The black suspension is placed in a water bath and stirred until the liquid is completely evaporated to obtain a solid phase.
[0010] 4) The solid phase material is transferred to a vacuum drying oven for drying, fully ground after drying, and transferred to a tubular furnace for high-temperature calcination to prepare a black powdery PdPtBiCuSn / C high entropy alloy catalyst.
[0011] Furthermore, the mass ratio of each metal element in the palladium source, platinum source, copper source, bismuth source and tin source described in step 1) is: m(Pd):m(Pt)=0.8~1.2, m(Cu):m(Bi):m(Sn)=1:1:1, m(Pd+Pt):m(Cu+Bi+Sn)=0.2~0.35, preferably m(Pd):m(Pt):m(Cu):m(Bi):m(Sn)=1:1:2:2:2.
[0012] Preferably, in step 1), the palladium source is palladium acetylacetonate or palladium chloride, the platinum source is platinum acetylacetonate or platinum chloride, the copper source is copper nitrate trihydrate or copper chloride, the bismuth source is bismuth nitrate pentahydrate, the tin source is stannous oxalate, and the strong acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution.
[0013] Preferably, the concentration of the strong acid aqueous solution in step 1) is 4 to 6 mol / L.
[0014] Preferably, the water bath temperature in step 3) is 50-85°C.
[0015] Preferably, the calcination atmosphere in the tubular furnace in step 4) is a hydrogen-argon mixed gas (hydrogen content 5%), the calcination temperature is 400-650° C., the heating rate is 5-10° C. / min, and the calcination time is 1-3 h.
[0016] Preferably, the potential range of the constant potential reaction is 0.5-1.0 V vs. RHE.
[0017] Preferably, the temperature range of the constant potential reaction is 5 to 30°C.
[0018] Preferably, the concentration range of potassium hydroxide or sodium hydroxide aqueous solution in the electrolyte is 0.1 to 3 mol / L.
[0019] Preferably, the concentration range of ethylene glycol in the electrolyte is 0.1 to 2 mol / L.
[0020] A high entropy alloy catalyst for preparing glycolate by efficient selective electrooxidation of ethylene glycol, wherein the total mass proportion of precious metal elements palladium and platinum in the PdPtBiCuSn / C high entropy alloy catalyst is 5-10wt%; and the mass proportion of activated carbon in the PdPtBiCuSn / C high entropy alloy catalyst is 50-70wt%.
[0021] In addition, the preparation methods in the present invention are all conventional methods unless otherwise specified, the raw materials used can be obtained from public commercial channels or prepared according to the prior art unless otherwise specified, the percentages are all mass percentages unless otherwise specified, and the solutions are all deionized water solutions unless otherwise specified.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The carbon-supported palladium platinum copper bismuth tin high entropy alloy nanoparticle (PdPtCuBiSn / C) catalyst provided by the present invention can selectively electrochemically convert ethylene glycol into glycolate with high activity, high selectivity and high stability. Specifically, it exhibits a high current density of 7590 mA mg at a working potential of about 0.8 V vs. RHE. P-t 1 +Pd The electrochemical mass activity is about 15 times and 3 times that of Pd / C and Pt / C with the same precious metal loading, respectively. PdPtCuBiSn / C exhibits an glycolate selectivity greater than 85% in the working potential range of 0.5-1.0V vs.RHE. Preferably, the glycolate selectivity of the high entropy alloy catalyst is 98.69% at a working potential of 0.8V vs.RHE.
[0024] 2. The method for preparing glycolate by electro-oxidation of ethylene glycol provided by the present invention has a simple process, readily available raw materials, and is environmentally friendly; in addition, the potential of high entropy alloys in electrocatalytic reactions can provide new solutions for green chemistry and clean energy technologies, and help reduce the impact of the chemical industry on the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention.
[0026] Figure 1 A physical picture of the PdPtCuBiSn / C high entropy alloy catalyst prepared in Example 1 is shown.
[0027] Figure 2 A high-resolution transmission electron microscope image of the PdPtCuBiSn / C high-entropy alloy catalyst prepared in the experimental group of Example 1 is shown.
[0028] Figure 3 The EDS element distribution image of the PdPtCuBiSn / C high entropy alloy catalyst prepared in Example 1 is shown.
[0029] Figure 4The X-ray diffraction spectrum of the PdPtCuBiSn / C high entropy alloy catalyst prepared in the experimental group of Example 1 is shown.
[0030] Figure 5 The cyclic voltammetry curve of ethylene glycol electrooxidation using the PdPtCuBiSn / C high entropy alloy catalyst prepared in Example 1 is shown.
[0031] Figure 6 The it curve during the electrolysis process of the electrolyte of Example 1 is shown.
[0032] Figure 7 The Faraday efficiency diagram of the electrolyte with PdPtCuBiSn / C high entropy alloy catalyst anode in Example 1 at different voltages is shown. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments. Obviously, the described implementation manner is only a part of the implementation manner of the present invention, rather than all the implementation manners.
[0034] There is no particular limitation on the purity of all raw materials in the present invention, and analytical purity is preferably adopted in the present invention.
[0035] The sources and abbreviations of all raw materials in the present invention are conventional sources and abbreviations in the field, and are clear and definite in the field of their relevant uses. Those skilled in the art can purchase them from commercial sources or prepare them by conventional methods based on the abbreviations and corresponding uses.
[0036] Example 1
[0037] A method for preparing a high entropy alloy catalyst for preparing glycolate by selective electrooxidation of ethylene glycol and its specific application, comprising the following steps:
[0038] 14.32 mg of palladium acetylacetonate, 10.10 mg of platinum acetylacetonate, 39.02 mg of copper nitrate trihydrate, 34.82 mg of stannous oxalate, and 23.2 mg of bismuth nitrate pentahydrate were weighed and dissolved in a strong acid aqueous solution consisting of 6 mg of water and 1.2 ml of concentrated HCl, 60.00 mg of activated carbon was added thereto, and ultrasonicated in an ultrasonic cleaning machine for 60 min to obtain a uniformly dispersed black suspension;
[0039] The black suspension was placed in a 70°C water bath and stirred continuously until the liquid was completely evaporated, then vacuum dried at 60°C for 12 hours to obtain a solid phase. The solid phase was fully ground and transferred to a tube furnace. Argon was introduced into the tube furnace for deoxygenation for 30 to 40 minutes, and the gas was switched to a hydrogen-argon mixed gas with a hydrogen content of 5%, and the temperature was raised to 650°C at a rate of 9°C / min and maintained for 3 hours, and then cooled to room temperature. Finally, a black powdered PdPtCuBiSn / C high entropy alloy catalyst with a theoretical noble metal loading of 10wt% was obtained.
[0040] The powder catalyst was loaded on a glassy carbon electrode by a drop coating method as a PdPtBiCuSn / C catalyst electrode for efficient ethylene glycol selective electrooxidation to prepare glycolate, which exhibited excellent electrocatalytic activity, stability and glycolate selectivity.
[0041] Example 2
[0042] A method for preparing a high entropy alloy catalyst for preparing glycolate by selective electrooxidation of ethylene glycol and its specific application, comprising the following steps:
[0043] 7.16 mg of palladium acetylacetonate, 5.05 mg of platinum acetylacetonate, 19.51 mg of copper nitrate trihydrate, 17.41 mg of stannous oxalate, and 11.6 mg of bismuth nitrate pentahydrate were weighed and dissolved in a strong acid aqueous solution consisting of 6 mg of water and 1.2 ml of concentrated HCl, 80.00 mg of activated carbon was added thereto, and ultrasonicated in an ultrasonic cleaning machine for 60 min to obtain a uniformly dispersed black suspension;
[0044] The black suspension was placed in a 70°C water bath and stirred continuously until the liquid was completely evaporated, then vacuum dried at 60°C for 12 hours to obtain a solid phase. The solid phase was fully ground and transferred to a tube furnace. Argon was introduced into the tube furnace for deoxygenation for 30 to 40 minutes, and the gas was switched to a hydrogen-argon mixed gas with a hydrogen content of 5%, and the temperature was raised to 650°C at a rate of 9°C / min and maintained for 3 hours, and then cooled to room temperature. Finally, a black powdered PdPtCuBiSn / C high entropy alloy catalyst with a theoretical noble metal loading of 5wt% was obtained.
[0045] The powder catalyst was loaded on a glassy carbon electrode by a drop coating method as a PdPtBiCuSn / C catalyst electrode for efficient ethylene glycol selective electrooxidation to prepare glycolate, which exhibited excellent electrocatalytic activity, stability and glycolate selectivity.
[0046] Example 3
[0047] A method for preparing a high entropy alloy catalyst for preparing glycolate by selective electrooxidation of ethylene glycol and its specific application, comprising the following steps:
[0048] 14.32 mg of palladium acetylacetonate, 10.10 mg of platinum acetylacetonate, 39.02 mg of copper nitrate trihydrate, 34.82 mg of stannous oxalate, and 23.2 mg of bismuth nitrate pentahydrate were weighed and dissolved in a strong acid aqueous solution consisting of 6 mg of water and 1.2 ml of concentrated HCl, 60.00 mg of activated carbon was added thereto, and ultrasonicated in an ultrasonic cleaning machine for 60 min to obtain a uniformly dispersed black suspension;
[0049] The black suspension was placed in a 70°C water bath and stirred continuously until the liquid was completely evaporated, then vacuum dried at 60°C for 12 hours to obtain a solid phase. The solid phase was fully ground and transferred to a tube furnace. Argon was introduced into the tube furnace for deoxygenation for 30 to 40 minutes, and the gas was switched to a hydrogen-argon mixed gas with a hydrogen content of 5%, and the temperature was raised to 500°C at a rate of 9°C / min and maintained for 3 hours, and then cooled to room temperature. Finally, a black powdered PdPtCuBiSn / C high entropy alloy catalyst with a theoretical noble metal loading of 10wt% was obtained.
[0050] The powder catalyst was loaded on a glassy carbon electrode by a drop coating method as a PdPtBiCuSn / C catalyst electrode for efficient ethylene glycol selective electrooxidation to prepare glycolate, which exhibited excellent electrocatalytic activity, stability and glycolate selectivity.
[0051] Comparative Example 1
[0052] In order to highlight the beneficial effects of the present invention, this comparative example 1 is provided, in which the five-element high entropy alloy catalyst prepared in Examples 1-3 of the present invention is compared with the single-component Pd / C catalyst, and the effect of the present invention on the selective electro-oxidation of ethylene glycol to prepare glycolate is intuitively reflected. The preparation method of comparative example 1 is as follows:
[0053] Weigh 28.64 mg of acetylacetonate palladium and dissolve it in a strong acid aqueous solution consisting of 6 mg of water and 1.2 ml of concentrated HCl, add 90.00 mg of activated carbon, and ultrasonicate it in an ultrasonic cleaning machine for 60 minutes to obtain a uniformly dispersed black suspension;
[0054] The black suspension was placed in a 70°C water bath and stirred continuously until the liquid was completely evaporated, then vacuum dried at 60°C for 12 hours to obtain a solid phase. The solid phase was fully ground and transferred to a tube furnace. Argon was introduced into the tube furnace for deoxygenation for 30 to 40 minutes, and the gas was switched to a hydrogen-argon mixed gas with a hydrogen content of 5%, and the temperature was raised to 650°C at a rate of 9°C / min and maintained for 3 hours, and then cooled to room temperature. Finally, a black powdered Pd / C catalyst with a theoretical noble metal loading of 10wt% was obtained.
[0055] The powder catalyst was loaded on a glassy carbon electrode by a drop coating method as a Pd / C catalyst electrode for efficient selective electro-oxidation of ethylene glycol to prepare glycolate. The electrocatalytic activity, stability and glycolate selectivity exhibited by the electrode were significantly lower than those of the PdPtCuBiSn / C high entropy alloy catalyst.
[0056] Comparative Example 2
[0057] In order to highlight the beneficial effects of the present invention, this comparative example 2 is provided, in which the five-element high entropy alloy catalyst prepared in Examples 1-3 of the present invention is compared with the single-component Pt / C catalyst, and the effect of the present invention on the selective electro-oxidation of ethylene glycol to prepare glycolate is intuitively reflected. The preparation method of comparative example 1 is as follows:
[0058] Weigh 20.20 mg of platinum acetylacetonate and dissolve it in a strong acid aqueous solution consisting of 6 mg of water and 1.2 ml of concentrated HCl, add 90.00 mg of activated carbon, and ultrasonicate it in an ultrasonic cleaning machine for 60 minutes to obtain a uniformly dispersed black suspension;
[0059] The black suspension was placed in a 70°C water bath and stirred continuously until the liquid was completely evaporated, then vacuum dried at 60°C for 12 hours to obtain a solid phase. The solid phase was fully ground and transferred to a tube furnace. Argon was introduced into the tube furnace for deoxygenation for 30 to 40 minutes, and the gas was switched to a hydrogen-argon mixed gas with a hydrogen content of 5%, and the temperature was raised to 650°C at a rate of 9°C / min and maintained for 3 hours, and then cooled to room temperature. Finally, a black powdered Pt / C catalyst with a theoretical noble metal loading of 10wt% was obtained.
[0060] The powder catalyst was loaded on a glassy carbon electrode by a drop coating method as a Pd / C catalyst electrode for efficient selective electro-oxidation of ethylene glycol to prepare glycolate. The electrocatalytic activity, stability and glycolate selectivity exhibited by the electrode were significantly lower than those of the PdPtCuBiSn / C high entropy alloy catalyst.
[0061] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
[0062] Table 1 Ethylene glycol electrooxidation performance data of catalysts
[0063]
Claims
1. A method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electro-oxidation of ethylene glycol, characterized in that: Here are the steps: a. The palladium source, platinum source, copper source, bismuth source and tin source are dissolved in a strong acid aqueous solution, and then activated carbon powder is added thereto and mixed by ultrasound to obtain a black suspension; The mass ratio of each metal element in the palladium source, platinum source, copper source, bismuth source and tin source is: m(Pd):m(Pt)=0.8-1.2, m(Cu):m(Bi):m(Sn)=1:1:1, m(Pd+Pt):m(Cu+Bi+Sn)=0.2-0.35, preferably m(Pd):m(Pt):m(Cu):m(Bi):m(Sn)=1:1:2:2:2; The concentration range of the strong acid aqueous solution is 4 to 6 mol / L; b. The black suspension was stirred at a certain temperature to evaporate the water, and then vacuum dried to obtain a solid phase, and the solid phase was fully ground and placed in a tube furnace for high temperature calcination to obtain a black powdered PdPtBiCuSn / C catalyst; The total weight percentage of the noble metal elements palladium and platinum in the PdPtBiCuSn / C high entropy alloy catalyst is 5% to 10wt%; The mass proportion of activated carbon in the PdPtBiCuSn / C high entropy alloy catalyst is 50-70wt%; c. PdPtBiCuSn / C powder was loaded on a glassy carbon electrode by drop coating as a PdPtBiCuSn / C catalyst electrode for efficient ethylene glycol selective electrooxidation to prepare glycolate.
2. The method for preparing a high entropy alloy catalyst for preparing glycolate by selective electrooxidation of ethylene glycol according to claim 1, characterized in that: Preferably, the palladium source is palladium acetylacetonate or palladium chloride; Preferably, the platinum source is platinum acetylacetonate or platinum chloride; Preferably, the copper source is copper nitrate trihydrate or copper chloride; Preferably, the bismuth source is bismuth nitrate pentahydrate; Preferably, the tin source is stannous oxalate; Preferably, the strong acid aqueous solution is hydrochloric acid or sulfuric acid aqueous solution.
3. The method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electro-oxidation of ethylene glycol according to claim 1, characterized in that: Potential range of constant potential reaction: 0.5~1.0V vs.RHE; The temperature range of constant potential reaction is 5~30℃.
4. The method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electro-oxidation of ethylene glycol according to claim 1, characterized in that: The concentration range of potassium hydroxide aqueous solution in the electrolyte is 0.1 to 3 mol / L; The concentration range of ethylene glycol in the electrolyte is 0.1 to 2 mol / L.
5. The method for preparing a high entropy alloy catalyst for preparing glycolate by efficient selective electro-oxidation of ethylene glycol according to claim 1, characterized in that: Stirring temperature range: 50~85℃; Calcination atmosphere in the tubular furnace: hydrogen-argon mixed gas (hydrogen content 5%); Tube furnace calcination temperature range: 400-650°C, heating rate 5-10°C / min; Tubular furnace calcination time range: 1 to 3 hours.